Upregulation of EGFR signaling is correlated with tumor stroma remodeling and tumor recurrence in FGFR1-driven breast cancer. Issue 1 (December 2015) - Holdman, Xue; Welte, Thomas; Rajapakshe, Kimal; Pond, Adam; Coarfa, Cristian; Mo, Qianxing; Huang, Shixia; Hilsenbeck, Susan; Edwards, Dean; Zhang, Xiang; Rosen, Jeffrey
Abstract Introduction Despite advances in early detection and adjuvant targeted therapies, breast cancer is still the second most common cause of cancer mortality among women. Tumor recurrence is one of the major contributors to breast cancer mortality. However, the mechanisms underlying this process are not completely understood. In this study, we investigated the mechanisms of tumor dormancy and recurrence in a preclinical mouse model of breast cancer. Methods To elucidate the mechanisms driving tumor recurrence, we employed a transplantable Wnt1/inducible fibroblast growth factor receptor (FGFR) 1 mouse mammary tumor model and utilized an FGFR specific inhibitor, BGJ398, to study the recurrence after treatment. Histological staining was performed to analyze the residual tumor cells and tumor stroma. Reverse phase protein array was performed to compare primary and recurrent tumors to investigate the molecular mechanisms leading to tumor recurrence. Results Treatment with BGJ398 resulted in rapid tumor regression, leaving a nonpalpable mass of dormant tumor cells organized into a luminal and basal epithelial layer similar to the normal mammary gland, but surrounded by dense stroma with markedly reduced levels of myeloid-derived tumor suppressor cells (MDSCs) and decreased tumor vasculature. Following cessation of treatment the tumors recurred over a period of 1 to 4 months. The recurrent tumors displayed dense stroma with increased collagen, tenascin-C expression, and MDSC infiltration. Activation of the epidermal growth factor receptor (EGFR) pathway was observed in recurrent tumors, and inhibition of EGFR with lapatinib in combination with BGJ398 resulted in a significant delay in tumor recurrence accompanied by reduced stroma, yet there was no difference observed in initial tumor regression between the groups treated with BGJ398 alone or in combination with lapatinib. Conclusion These studies have revealed a correlation between tumor recurrence and changes of stromal microenvironment accompanied by altered EGFR signaling.